Symposium policy note 3: Cash transfers as an effective tool for social protection and shock response in Egypt - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This policy note is one in a series of four notes that summarizes key findings and recommendations from 32 seminars that IFPRI organized between 2016 and 2020 under the Evaluating Impact and Building Capacity Project funded by the United States Agency for International Development (USAID) and from related research done in collaboration with national and international partners in Egypt. The briefs have been prepared on the basis of a joint symposium and are intended to give policy makers and program designers in the areas of social protection, nutrition, agricultural policy, and the digitalization of agriculture a quick overview of research-based recommendations on key policy issues that will better enable Egypt achieve several of the goals outlined in the Sustainable Development Strategy 2030. Social protection programs are essential for supporting Egyptians who are economically the most vulnerable. This brief makes the argument for moving more decisively toward a cash-based social protection system in Egypt. Four areas of action are highlighted: Continue the well-functioning Takaful and Karama program and consider increasing its budget to adjust transfers to inflation. Consider improving the targeting for Tamween food subsidies and integrating Takaful and Karama with Tamween. Continue the use of transparent and independent impact evaluations to assess social protection programs in order to maximize their benefits for Egypt and its people. Maintain the ability to respond flexibly to future shocks as an important feature of solidifying the national social protection system.